OSHA Regulation Summary (Tufts Archival Research Center, 2007)
Summary of OSHA regulation. Includes details of regulations and relevant OSHA definitions. Identifies opposing organizations and summarizes the rationale behind their opposition. Lists some workplaces that wil be subject to regulations. Cites special situations.